Rosai–Dorfman disease presenting as mediastinal lymphadenopathy: case report and review of the literature. (May 2013) - Cobanoglu, Nazan; Galip, Nilufer; Dalkan, Ceyhun; Comunoglu, Cem; Bahceciler, Nerin
Abstract : A 6-year-old boy presented with recurrent pneumonia and diarrhoea for 3 years. He had extensive mediastinal lymphadenopathy and atelectasis with low serum levels of IgA, IgG and IgG3. An inguinal lymph node biopsy demonstrated histological and histochemical features of Rosai–Dorfman disease. There was emperipolesis and histiocytes were immune-positive for S100 proteins. He responded to corticosteroids and regular infusions of immunoglobulins.